Brazilian Development in Long-Term Perspective - Fishlow, Albert (American Economic Review, 2016)
Brazil is now the eighth largest market economy in the world. Its 1979 per capita income of over $1,500 in current dollars, its sophisticated industrial structure, and its recent dynamism combine to give it a prominent place among the advanced developing countries. Not surprisingly, recent Brazilian experience has been an important subject for the analysis of economic development, not all of it uncritical. Such a focus on the Brazilian miracle and its aftermath is too limited. Brazilian growth and industrialization have a long history as do the regional and personal income inequalities that today increasingly command attention. Understanding the origins of Brazilian growth in the nineteenth-century export economy and the subsequent patterns of import substitution will not yield better rules for short-term debt management or monetary policy. But the longer perspective makes clear that sustained economic development requires more than following the dictates of the international market and getting prices right. Indeed it may on occasion involve rejecting such signals. I shall interpret four significant episodes